The Tools We Don’t Have: Future and Current Inventory Management in a Room Reservation System - Denis Galvin; Mang Sun; Hanjun Lee (Code4Lib Journal, 2018)
Fondren Library at Rice University has numerous study rooms which are very popular with students. Study rooms, and equipment, have future inventory needs which require a visual calendar for reservation. Traditionally libraries’ manage reservations through a booking module in an Integrated Library System (ILS), but most, if not all, booking modules lack a visual calendar which allows patrons to pick out a place and time to create a reservation. The IT department at Fondren library was able to overcome this limitation by modifying the open source Booked Scheduling software so that it did all of the front end work for the ILS, while still allowing the ILS to manage the use of the rooms.